Wage and Employment Cyclicalities at the Establishment Level - Christian Merkl; Heiko Stüber (Center for Economic Studies and ifo Institute (CESifo), 2021)
We document substantial cross-sectional heterogeneity of German establishments' real wage cyclicality over the business cycle. While wages of the median establishment are moderately procyclical, 36 percent of establishments have countercyclical wages. We estimate a negative connection between establishments' wage cyclicality and their employment cyclicality, thereby providing a benchmark for quantitative macroeconomic models. We propose and calibrate a labor market flow model to match various empirical facts and to perform counterfactual exercises. If all establishments behaved as the most procyclical ones, labor market amplification would drop by one-third. If all followed Nash bargaining, it would drop by more than two-thirds.
Keywords: E32; E24; J64; 330; wage cyclicality; employment cyclicality; labor market flow model; labor market dynamics; establishments; administrative data